Correlation Between Intravenous Catheter Related Infections And Biofilms In Staphylococcus Epidermidis - PRACHI SHAW; CHANDAN KUMAR SHAW; K. SAILEELA (International Journal of Pharma and Bio Sciences, 2012)
S. epidermidis is commonly associated with catheter related sepsis with a unique property of biofilm formation. This genetically determined property aids its survival by the phenomenon of immune evasion. In all, IV catheter tips and two synchronous blood samples from 297 patients with intravenous catheters and ≥ 48 hours stay in KIMS were subjected to culture and biofilm formation by S. epidermidis strains thus isolated. Biofilm formation was correlated with the clinical presentation of the cases grouped as “septicemia” or “asymptomatic” - with or without thrombophlebitis. The results were compared using the χ2 test. Out of these 297 samples, S. epidermidis was isolated from 62 catheter tips (20.9%) and simultaneously from blood cultures (septicemia) and I.V. catheter tips from same patients in 38 cases (12.8%) all of which were associated with septicemia. Biofilm was demonstrated in 63.2% of 38 cases of culture proven septicemia as well as I.V. catheter tip positivity, significantly higher, compared to 25% of 24 isolates from catheter tip only. (p value < 0.005). The incidence of biofilm forming S. epidermidis in cases with thrombophlebitis was 17.1% not significantly different than in the cases without thrombophlebitis was 18.5%. (p value > 0.05). Thirty out of the 62 isolates (48.4%) from I.V. catheter tips from cases in the “septicemia group” were biofilm formers while 20.8% of the isolates from “asymptomatic group” were biofilm formers (p value < 0.05) whereas 25.0% were positive for biofilm formation exclusive I.V. Catheter tip positivity.(p value >0.05). Biofilm formation by isolates of S. epidermidis was found to be significantly more common in cases with culture proven sepsis than with those with only I.V. catheter tip positivity. Biofilm formation by S. epidermidis isolates does correlate significantly with cases with clinical signs and symptoms of sepsis but not so with local signs like thrombophlebitis.